Effect of Muskox Carcasses on Nitrogen Concentration in Tundra Vegetation - Danell, Kjell; Berteaux, Dominique; Bråthen, Kari Anne (ARCTIC, 2002)
We observed a steep gradient of nitrogen concentration in plants growing around carcasses of four adult muskoxen that had been lying for five or more years on the tundra in the Canadian Arctic. The gradient reached an asymptote at 2 m distance from the carcasses. The carbon-to-nitrogen ratio increased significantly from 1 to 3 m and then stabilized. These results suggest that the effects of carcasses last for several years on the tundra and create nitrogen-rich plant growth in their immediate surroundings. The lush growth around the carcasses in otherwise grazed areas indicated a low level of grazing on the fertilized plants. Nous avons observé un fort gradient de concentration en azote dans les plantes poussant autour de 4 carcasses de bœufs musqués gisant depuis 5 ans ou plus dans la toundra de l'Arctique canadien. Le gradient atteignait une asymptote à 2 m des carcasses. Le rapport carbone/azote augmentait de façon significative de 1 à 3 m, puis se stabilisait. Nos résultats suggèrent que les carcasses créent dans la toundra des micro-communautés de plantes riches en azote dans leur environnement immédiat et que cet effet dure plusieurs années. L'abondance de végétation autour des carcasses, dans des endroits autrement broutés, révélait que les herbivores utilisaient peu les communautés végétales fertilisées.